Design and Implementation of Intelligent City Smoke Filter - P. Aruna Jeyanthy, Jawahar Akash A., Vasanth J. Loksai Teja P. (International Journal of Advanced Science and Technology, 2020)
Intelligent city smoke filter is aimed to eliminate smoke from city in an efficient way. We provide algorithm to tackle smoke emissions of automobiles. Individual group of intelligent city smoke filter will be fixed in a place which is receiving high intensity of smoke. Filtering smoke from different places in a small amount will be helpful in dealing with huge air pollution. Product has to be fabricated in a way that it has to be maintained with ease. Less labor interaction with a device leads to cost cutting in maintenance. Small products can be easily installed and replaced. Intelligent smoke filter consists of filter and electronics. Electronics consists of Arduino, GSM module, Display, Rectifier, Transformer, Dust sensor, fan. Fan and filter are connected in parallel. Adjacent to filter dust sensor is connected. Dust sensor senses amount of dust deposited on the filter. If the amount of dust particle (PM) increases inside the filter through dust sensor, Arduino senses the level, if the threshold level reached it sends information to maintenance team through GSM module for replacement of filter. Display is used to show real-time (PM) particulate matter, dust readings through Arduino with the help of dust sensor. 230 v AC is given to fan. With the help of this project we can give better environment to the society.